A comparative study of viral capsids and bacterial compartments reveals an enriched understanding of shell dynamics. Issue 2 (16th November 2017) - Song, Guang
Abstract: In this work, we carry out a comparative study of the homo 360‐mer structures of viral capsids and bacterial compartments. Different from viral 360‐mers that all are arranged on a skewed right‐handed icosahedral lattice with a triangulation number T of 7, the new 360‐mer structure of AaLS‐13, an engineered bacterial compartment, offers a novel open conformation that has a unique unskewed lattice arrangement with a triangulation number T of 1 and large keyhole‐shaped pores in the shell. By comparing their differences, we are able to predict a closed conformation of AaLS‐13 that has the same lattice arrangement as existing viral capsid structures and in which all the keyhole‐shaped pores are shut. We find that there is a smooth transition pathway between the open and closed conformations. There exists another close conformation but with an opposite, left handedness, which, however, is not kinetically accessible from the open conformation. Our finding thus provides a clue why existing 360‐mer capsid structures all share the same right handedness. We further show that the conformation transition between the open and closed forms aligns extremely well with the intrinsic dynamics of the system as revealed from normal mode analysis, indicating that conformation transition can be fully driven by thermal fluctuations. The significance of this work is that it provides a better understanding of shell dynamics of both viral capsids and bacterial compartments, paving a way for future study of pore dynamics and the selective permeability of these systems.